Prognosis of Acute Kidney Injury and Hepatorenal Syndrome in Patients with Cirrhosis: A Prospective Cohort Study. (22nd July 2015) - Allegretti, Andrew S.; Ortiz, Guillermo; Wenger, Julia; Deferio, Joseph J.; Wibecan, Joshua; Kalim, Sahir; Tamez, Hector; Chung, Raymond T.; Karumanchi, S. Ananth; Thadhani, Ravi I.
Abstract : Background/Aims . Acute kidney injury is a common problem for patients with cirrhosis and is associated with poor survival. We aimed to examine the association between type of acute kidney injury and 90-day mortality. Methods . Prospective cohort study at a major US liver transplant center. A nephrologist's review of the urinary sediment was used in conjunction with the 2007 Ascites Club Criteria to stratify acute kidney injury into four groups: prerenal azotemia, hepatorenal syndrome, acute tubular necrosis, or other. Results . 120 participants with cirrhosis and acute kidney injury were analyzed. Ninety-day mortality was 14/40 (35%) with prerenal azotemia, 20/35 (57%) with hepatorenal syndrome, 21/36 (58%) with acute tubular necrosis, and 1/9 (11%) with other (p = 0.04 overall). Mortality was the same in hepatorenal syndrome compared to acute tubular necrosis (p = 0.99 ). Mortality was lower in prerenal azotemia compared to hepatorenal syndrome (p = 0.05 ) and acute tubular necrosis (p = 0.04 ). Ten participants (22%) were reclassified from hepatorenal syndrome to acute tubular necrosis because of granular casts on urinary sediment. Conclusions . Hepatorenal syndrome and acute tubular necrosis result in similar 90-day mortality. Review of urinary sediment may add important diagnostic information to this population. Multicenter studies are needed to validate these findings and better guide management.